Nexus Among Knowledge Management, Organisational Ambidexterity, Innovation Capability, And Manufacturing Performance: A Study In Ir4.0 Focus Sectors - Cheah, Seng Cheong (2023)
Malaysia’s manufacturing sector is one of the main contributors to its GDP, but its growth rate has declined over the past few years. Challenge by neighbouring countries with lower labour costs, it has to improve its productivity by upskilling its human resources and adopting advanced manufacturing technologies that the fourth industrial revolution 4.0 (IR4.0) can offer. Realising the need to increase the adoption and diffusion of this new knowledge, the Malaysian government introduced two IR4.0 blueprints to facilitate the adoption of these advanced technologies. This research set out to investigate the relationship between knowledge management (KM), innovation capability (IC), organisational ambidexterity (OA) and manufacturing performance (MP) within this era. Large manufacturing firms from five IR4.0 focus sectors were selected for this study, and an online survey was carried out to gather the data. A total of 145 firms responded. IBM SPSS and Smart-PLS software were used for statistical analysis. The study reveals that OA and external knowledge sourcing (EKS) is key to achieving a better MP. Likewise, EKS and OA also positively impact IC. EKS, knowledge sharing (KS) and knowledge protection (KP) provide the basis of an ambidextrous organisation. EKS, KS, and KP were also found to impact IC and MP indirectly through OA.